Створення "Національного атласу України" як етап розвитку історико-географічних і картографічних знань в Інституті історії України НАН України - Марченко, О. (Історико-географічні дослідження в Україні, 2015)
У статті досліджується розвиток історико-географічних і картографічних студій в Інституті історії України НАН України за
радянської доби на прикладі створення «Національного атласу України» в УРСР. Аналізуються основні напрямки досліджень
учених Інституту історії АН УРСР у зазначений період. Підкреслюється формування історико-географічного осередку в Інституті
історії України НАН України в УРСР. В статье исследуется развитие историко-географических и картографических студий в Институте истории Украины НАН
Украины в советское время на примере создания «Национального атласа Украины» в УССР. Анализируются основные направления
исследований ученых Института истории АН УССР в данный период. Подчеркивается формирование историко-географической
ячейки в Институте истории Украины НАН Украины в УССР. The article highlights the development of historical and geographical
and cartographical studies in the Institute of History of Ukraine of
the National Academy of Sciences of Ukraine during creating the National
Atlas of Ukraine in the USSR. It provides analysis of the main
directions of research by scientists of the Institute of History of the
Academy of Sciences of the Ukrainian SSR in this period. Special emphasis
was made on the formation of historical and geographical nucleus
in the Institute of History of Ukraine of the National Academy of
Sciences of Ukraine in the USSR.